Sentido de la educación y el desarrollo humano: perspectiva educativa - Campos Arenas, Agustín (2014)
Education and human development are twointerrelated and interdependent concepts.Although, initially, human development wasconsidered with an econometrics vision;nowadays, it is considered being associatedto others components, specially education.Human development implies levels ofeducation and these are levels of humandevelopment.